IMPLEMENTATION OF LAW ENFORCEMENT OF HAND-CATCHING OPERATIONS (OTT) IN LAW NUMBER 19 OF 2019 - Aprilia Krisdayanti; Edelweiss Premaulidiani Putri (Universitas Islam kadiri, 2023)
Corruption in Indonesia is increasingly becoming a topic of discussion along with the debate over the revision of the KPK Law and the election of a new chairman of the